2010
DOI: 10.1080/15538361003676793
|View full text |Cite
|
Sign up to set email alerts
|

Soft Wood Grafting in Mandarin (C. reticulataBlanco): A Novel Vegetative Propagation Technique

Abstract: Studies were carried out at ICAR Research complex for NEH Region Umiam, Meghalaya, India on soft wood grafting in 'Khasi' mandarin under poly house, net house, and open field conditions at 15-day intervals from June 15 to October 15. Early sprouting, graft success, and scion growth were found to be better under poly house than other conditions. Similarly, the best graft success and early sprouting were observed to be better under the open condition than the net house, but growth performance of the plants was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Plant survival per cent was higher in Coorg mandarin grafted on three (98%) and four month's (98%) old rootstocks where as lowest plant survivability was noticed in one month old rootstocks (86.37 %). The higher survival on three and four months old rootstocks which may be due to strong stock-scion interaction which is very much necessary for water and essential nutrient flow (Prez-alfocea et al, 2010) and findings are in line with Deshmukh et al (2017) and Patel et al (2010).…”
Section: Resultssupporting
confidence: 56%
“…Plant survival per cent was higher in Coorg mandarin grafted on three (98%) and four month's (98%) old rootstocks where as lowest plant survivability was noticed in one month old rootstocks (86.37 %). The higher survival on three and four months old rootstocks which may be due to strong stock-scion interaction which is very much necessary for water and essential nutrient flow (Prez-alfocea et al, 2010) and findings are in line with Deshmukh et al (2017) and Patel et al (2010).…”
Section: Resultssupporting
confidence: 56%
“…Graftsuccess % ð Þ¼ Noofsproutedgrafts Totalnumberofgrafts � 100 (Patel et al, 2010;Chalise et al, 2013a).…”
Section: Graft Success (%)mentioning
confidence: 99%
“…Mandarin can be propagated by seed, cuttings, layering, grafting, or budding. Among the various vegetative methods used to propagate the mandarin, grafting is the most common method practiced in the Nepalese citriculture industry, as it results in the highest success and field establishment (Patel et al, 2010) in which veneer and side grafting are mostly practiced throughout the country (Pandey and Karki, 2019). However, the success of grafting is highly influenced by several factors like temperature, relative humidity, moisture, and plant water, the growth stage of scion and rootstock, method of grafting, and genetic relationship between the stock and the scion (Hartmann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among different times of T-budding the first week of September (T3) budded plants were (23.04 cm) long and when budding was practiced during first week of August (T2) the plants remained at the lowest height (21.11 cm) at 120 DAB. The research trial carried out by Patel et al (2007) wherein they observed that plant height was influenced by date of propagation. The higher content of auxins in the plants (Hartmann et al, 2007) was also responsible for plant height.…”
Section: Survival Percentagementioning
confidence: 99%